Unveiling Genital Tuberculosis: India’s hidden Infertility Epidemic - VR, Yashvanthan; Grace G, Angeline; P, Sujitha; T, Ilam Ilaval; S, Hariharan (National Journal of Community Medicine, 2025)
Genital tuberculosis (GTB) is a significant yet underrecognized cause of infertility, particularly in high-burden countries like India. It often presents asymptomatically or mimics other reproductive disorders, leading to delayed diagnosis and treatment. GTB primarily affects women of reproductive age but can also impact men, contributing to infertility through various pathophysiological mechanisms. Despite its prevalence, GTB remains a hidden epidemic due to limited awareness, diagnostic challenges, and systemic healthcare gaps. This narrative review explores the epidemiology, pathophysiology, clinical presentation, and impact of GTB on infertility in India. It also highlights diagnostic and management challenges while proposing strategies to address this critical public health issue. GTB contributes to 15-20% of infertility cases in India, with the highest burden among women aged 20-40 years. Hematogenous spread of Mycobacterium tuberculosis leads to chronic inflammation, fibrosis, and scarring of reproductive organs, resulting in irreversible damage. Traditional methods like microscopy and culture are inadequate for GTB detection. Advanced techniques, though more accurate, remain inaccessible to many due to cost and resource constraints. While antitubercular therapy (ATT) can control infection, restoring fertility often requires surgical intervention or assisted reproductive technologies, which are financially prohibitive for most patients. GTB is a silent epidemic with profound implications for reproductive health and social well-being in India. Addressing GTB requires enhanced awareness, integration of infertility screening into TB programs, improved access to advanced diagnostics and treatments, and targeted public health policies. Bridging these gaps can mitigate the burden of infertility and improve quality of life for affected individuals.